Manejo de la membrana hialina tipo i en un hospital general - Pilco Garcia, Dario Xavier (Machala : Universidad Técnica de Machala, 2019)
Introduction: Hyaline membrane disease (HMD) is a typical pathology of premature newborns, which is characterized by progressive respiratory difficulty that can appear in the first minutes of life caused by the deficit of pulmonary surfactant, becoming one of the major complications in neonates. General Objective: Explain the proper management for the hyaline membrane type I in a General Hospital, through the bibliographic review of articles indexed in Scimago and obtained through ScienceDirect, Pubmed, Google Scholar, to update information that could be useful in other medical professionals. Methodology: Firstly, the search engines are located to allow us to find scientific articles, then the search of the documents is done with the help of the aforementioned key words, then the period of publication time is skewed, fundamentally in recent years, as well as also the types of articles downloaded, finally the impact and prestige of scientific journals belonging to quartiles 1 and 2 (Q1 and Q2) is verified. Conclusions: The early use of nasal CPAP in preterm infants with hyaline membrane is highly justified, since it helps the neonate increasing the probabilities of survival and decreases complications mainly such as pulmonary bronchodilaplasia, ventilator-associated pneumonia, retinopathy, cerebellar hemorrhage.
Objetivo General: Explicar el manejo adecuado para la membrana hialina tipo I en un Hospital General, a través de la revisión bibliográfica de artículos indexados en Scimago y obtenidos a través de ScienceDirect, Pubmed, Google Scholar, para actualizarla información que podría ser útil en otros profesionales de la medicina. Metodología: Primeramente, se localiza los buscadores que nos permitan encontrar artículos científicos, luego se realiza la búsqueda de los documentos con ayuda de las palabras claves antes mencionadas, seguidamente se sesga el periodo de tiempo de publicación, fundamentalmente en los últimos años, así como también los tipos de artículos descargados, finalmente se verifica el impacto y prestigio de las revistas científicas que pertenezcan a los cuartiles 1 y 2 (Q1 y Q2). Conclusiones: El uso temprano de CPAP nasal en prematuros con membrana hialina se ve altamente justificado, ya que ayuda al neonato aumentando las probabilidades de supervivencia y disminuye complicaciones principalmente como la broncodisplasia pulmonar, neumonía asociada al ventilador, retinopatía, hemorragia cereblal.
Keywords: MEMBRANA HIALINA; SURFACTANTE; CPAP NASAL; DIFICULTAD RESPIRATORIA